Israels Forensic Science Service: Organizational Structure and Training of Personnel – The Example of the Latent Fingerprints Laboratory - Boris Geller (Теория и практика судебной экспертизы)
An overview of Israel's national forensic science service includes its history, current structure, system of employee recruitment and training, and organization of main operations, international collaboration and scientific research.